Enigma of Increasing Value Added Taxes in Middle of Development Countries Conflict Based on Pancasila Perspective Justice - Yazid Bustomi; Alma Evelinda Silalahi (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2023)
Through Law Number 7 of 2021 concerning the Harmonization of Tax Regulations (HPP Law), the Value Added Tax (VAT) has increased which has resulted in polemics in the community. The increase in VAT coincides with the rise of the country after the COVID-19 pandemic and conflicts between developed countries. This is a normative research type using secondary data consisting of primary legal materials in the form of legislation and secondary legal materials, namely literature. The collection of legal materials is carried out by library research. The data processing technique is carried out by the syllogism method using deductive thinking patterns. The results of the study stated that the increase in VAT through the HPP Law was in accordance with Pancasila Justice. The US-China conflict for Indonesia has significant implications for the Indonesian economy, especially in the export sector and stock investment. The Russian-Ukrainian conflict for Indonesia has implications for trade performance and a severe impact is the increase in global energy prices. This increase put pressure on fiscal conditions. With the increase in VAT, this is a social engineering carried out by the government to change lives for the better. The formulation of Pancasila justice is that the state has a dual role to protect the obligations and rights of its people. Due to limited power, the dual role cannot be carried out by the state so that it requires mutual cooperation with the people so that justice can be achieved. The fact that is not realized through the increase in VAT is that economic democracy: from the people by the people and for the people; then social welfare will be achieved. Keywords: Justice, Pancasila, Tax, VAT